2006
DOI: 10.1111/j.1537-2995.2006.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an immunoglobulin A–deficient blood donor registry with a simple in‐house screening enzyme‐linked immunosorbent assay

Abstract: With a simple in-house ELISA, 73 blood donors were identified as IgA-deficient. From this number, 34 donors, without detectable anti-IgA in their plasma, were added to our IgA-deficient blood donor panel to maximize the management of our inventory of IgA-deficient frozen blood components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Many anti-IgA antibodies occur naturally; in one study, only 9 out of the 39 blood donors with detectable anti-IgA antibodies had a history of transfusion or pregnancy. 6 It could be that sensitisation occurs in utero by maternal IgA crossing the placenta and entering the foetal circulation. Alternatively, human breast milk IgA, or bovine IgA, could be absorbed via the intestinal wall and cause sensitisation.…”
Section: Discussionmentioning
confidence: 99%
“…Many anti-IgA antibodies occur naturally; in one study, only 9 out of the 39 blood donors with detectable anti-IgA antibodies had a history of transfusion or pregnancy. 6 It could be that sensitisation occurs in utero by maternal IgA crossing the placenta and entering the foetal circulation. Alternatively, human breast milk IgA, or bovine IgA, could be absorbed via the intestinal wall and cause sensitisation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many registries of blood donors with IgA deficiency have been established in different countries [4,5,6]. Nevertheless, anaphylactic reactions due to anti-IgA cannot invariably be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that such reactions can be prevented by providing IgA-deficient blood components collected from IgA-deficient blood donors. Based on this option, registries of such donors have been established in the USA, Canada, and some countries in Europe and Asia [4,5,6,7]. However, in practice, the use of these rare products cannot be realized in many instances, particularly in emergencies or where platelets are required [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is because autologous blood is not available for patients with excessive blood loss, and washing RBCs and PLTs is timeconsuming, laborious and limits their activity. Many countries have developed large-scale detection methods for IgA deficiency, and registries of IgA-deficient donors have been established in Canada, the United States and in some European countries (Thibault et al, 2006). These actions support the rare occurrence of IgA-negative blood transfusion to IgA-deficient persons, minimising the incidence rate of adverse transfusion reactions and enhancing blood safety.…”
mentioning
confidence: 99%